Fear Assessment in Inflammatory Rheumatic diseases (FAIR) questionnaire: A cross-cultural adaptation and validation to the Turkish language - Küçükakkaş, Okan; Rezvani, Aylin; Yurdakul, Ozan Volkan; Tolu, Sena; Kılıçoğlu, Mehmet Serkan; Aydın, Teoman (Springer London Ltd, 2018)
In chronic inflammatory rheumatic diseases (CIRD), it is important to understand patients' fears towards their disease in order to improve patient-physician dialog, to raise the quality of care offered, and to optimize treatment adherence. In this study, we aimed to translate the Fear Assessment in Inflammatory Rheumatic diseases (FAIR) questionnaire into Turkish and evaluate its psychometric properties in patients with CIRD. One hundred fifteen patients filled the provided socio-demographic information form, FAIR-Tr questionnaire, Hospital Anxiety and Depression Scale (HADS), and Beck's Hopelessness Scale (BHS). For the analysis of short-term reliability, 50 patients re-filled the FAIR-Tr questionnaire 1week later. Internal consistency was evaluated with Cronbach's coefficient and test-retest reliability was evaluated with intraclass correlation coefficients (ICC). Construct validity analysis was investigated based on the correlation with HADS and BHS. All patients found FAIR-Tr easily understandable and acceptable. FAIR-Tr internal consistency (Cronbach's =0.93) and test-retest reliability (ICC=0.91) were excellent. Psychometric validation was proved upon observing high correlation with HADS (Anxiety, r=0.77; Depression, r=0.70) and moderate correlation with BHS (r=0.65). FAIR-Tr is a questionnaire that has excellent internal consistency and test-retest reliability. The successful correlation with HADS and BHS supported its psychometric validity in terms of evaluating the fear in CIRD cases. We think that FAIR-Tr is a specific scale that can help to evaluate the disease- and treatment-related fears of the Turkish patients with CIRD and may be useful in both routine practice and clinical studies.
WOS: 000451729300012
PubMed ID: 30054752
Keywords: Chronic İnflammatory Rheumatic Diseases; Cross-Cultural Adaptation; Fears; Psychometric Properties; Reliability; Turkish language; Validity